Influence of Silane‐Treated Jute/Kenaf Fibers on the Mechanical Properties of Polymer Composites for Biomedical Applications: Optimization Using RSM and ANN Approaches - R. Saravanan; S. Jothi Arunachalam; T. Sathish; Jayant Giri; Muhammad Imam Ammarullah (Engineering Reports)
ABSTRACT This study investigates the effect of silane‐treated jute/kenaf fibers on the flexural and hardness properties of polymer composites for potential biomedical applications, such as prosthetics and bio‐implants. Using response surface methodology (RSM) and artificial neural network (ANN), the optimal combination of nanoparticle percentage, silane concentration, and silane dipping duration was identified to enhance the mechanical properties of the composites. RSM, coupled with analysis of variance (ANOVA), evaluated the influence of these variables on composite performance, revealing that silane treatment significantly improved flexural strength, while all fiber‐related variables impacted both flexural strength and hardness. The silane dipping duration emerged as the most influential factor, with nanoparticle addition enhancing fiber–matrix interactions and promoting better agglomeration. The ANN model accurately predicted the composite's properties, with results strongly correlating to experimental data. The optimized formulation, consisting of 5% nanoparticle content, 10% silane treatment, and a 20‐min silane dipping duration, demonstrated a 26.22% increase in flexural strength and a 33.15% improvement in hardness. This optimized composite formulation holds promise for use in biomedical applications requiring high mechanical strength and durability, such as in prosthetic materials and orthopedic implants, where enhanced flexural strength and hardness are critical for longevity and performance.